Expression of programmed cell death protein 1 (PD-1) and its ligand PD-L1 in colorectal cancer: Relationship with sidedness and prognosis. (3rd August 2018) - Berntsson, Jonna; Eberhard, Jakob; Nodin, Björn; Leandersson, Karin; Larsson, Anna H; Jirström, Karin
ABSTRACT: Expression of programmed cell death protein 1 (PD-1) and its ligand PD-L1 has been demonstrated to confer a prognostic value in colorectal cancer (CRC), but no studies have investigated whether this association differs according to tumour location. In this study, immunohistochemical expression of PD-1 and PD-L1 was analysed in tissue microarrays with primary tumours from 557 incident CRC cases from a prospective population-based cohort. Univariable and multivariable Cox regression analyses, adjusted for age, sex, TNM stage, differentiation grade and vascular invasion, were applied to determine the impact of biomarker expression on 5-year overall survival (OS), in the entire cohort and in subgroup analysis of right colon, left colon, and rectum. High PD-L1 expression on tumour-infiltrating immune cells was an independent factor of a prolonged OS in the entire cohort (hazard ratio [HR] = 0.49; 95% confidence interval [CI] CI 0.35 – 0.68), and in tumours of the right colon (HR = 0.43; 95% CI 0.25 – 0.74) and the left colon (HR = 0.28; 95% CI 0.13 – 0.61), but not in rectal cancer. Tumour-specific PD-L1-expression was not prognostic, neither in the full cohort nor according to tumour location. High immune cell-specific PD-1 expression was associated with a prolonged OS in the entire cohort and in tumours of the right colon, but not in the left colon or rectum, and only in univariable analysis. In conclusion, these results demonstrate that immune cell-specific PD-L1 and PD-1 expression is prognostic in a site-dependent manner, whereas tumour-specific PD-L1-expression is not prognostic in CRC.